Case Report: Targeted interleukin-6 blockade by siltuximab for cytokine release syndrome control and infection limitation in thirteen patients treated with bi-specific T-cell engagers - Rossi, Jean-François; Cailleux, Thierry; Wisnewski, Emma; Coussirou, Julie; de Crozals, Françoise (Frontiers in Immunology, 2026)
Infections remain a major concern during treatment with bispecific T-cell engagers (BiTE) in hematological malignancies. The risk is primarily driven by disease- and treatment-related immunosuppression, as well as corticosteroid use during the early phase of therapy. It persists throughout the treatment course, requiring appropriate prophylactic measures. We report a real-world series of thirteen patients treated with BiTEs: 10 with multiple myeloma, two with refractory AL amyloidosis, and one with mantle cell lymphoma. During initial hospitalization, daily C-Reactive protein (CRP) monitoring was performed. Siltuximab, an anti-interleukin-6 monoclonal antibody, was administered instead of corticosteroids when CRP exceeded 40 mg/L with a rapid 24-hour increase, based on predictive mathematical modeling, to preempt cytokine release syndrome (CRS). All patients received standard anti-infective prophylaxis, and treatment duration was adapted to clinical response. This approach was associated with only three grade 1–2 infections, indicating a favorable safety profile. These preliminary results support the design of a prospective multicenter study to evaluate the feasibility of home-based BiTE administration, integrating point-of-care testing, a digital health platform, and 24/7 remote monitoring via a dedicated call center, within a comprehensive medico-economic framework.